Cyclooxygenase‐2 Regulates NLRP3 Inflammasome‐Derived IL‐1β Production. Issue 4 (April 2015) - Hua, Kuo‐Feng; Chou, Ju‐Ching; Ka, Shuk‐Man; Tasi, Yu‐Ling; Chen, Ann; Wu, Shih‐Hsiung; Chiu, Hsiao‐Wen; Wong, Wei‐Ting; Wang, Yih‐Fuh; Tsai, Change‐Ling; Ho, Chen‐Lung; Lin, Cheng‐Hsiu
<x xml:space="preserve">Abstract</x> The NLR family, pyrin domain‐containing 3 (NLRP3) inflammasome is a reactive oxygen species‐sensitive multiprotein complex that regulates IL‐1β maturation via caspase‐1. It also plays an important role in the pathogenesis of inflammation‐related disease. Cyclooxygenase‐2 (COX‐2) is induced by inflammatory stimuli and contributes to the pathogenesis of inflammation‐related diseases. However, there is currently little known about the relationship between COX‐2 and the NLRP3 inflammasome. Here, we describe a novel role for COX‐2 in regulating the activation of the NLRP3 inflammasome. NLRP3 inflammasome‐derived IL‐1β secretion and pyroptosis in macrophages were reduced by pharmaceutical inhibition or genetic knockdown of COX‐2. COX‐2 catalyzes the synthesis of prostaglandin E2 and increases IL‐1β secretion. Conversely, pharmaceutical inhibition or genetic knockdown of prostaglandin E2 receptor 3 reduced IL‐1β secretion. The underlying mechanisms for the COX‐2‐mediated increase in NLRP3 inflammasome activation were determined to be the following: (1) enhancement of lipopolysaccharide‐induced proIL‐1β and NLRP3 expression by increasing NF‐κB activation and (2) enhancement of the caspase‐1 activation by increasing damaged mitochondria, mitochondrial reactive oxygen species production and release of mitochondrial DNA into cytosol. Furthermore, inhibition of COX‐2 in mice in vivo with celecoxib reduced serum levels of IL‐1β and caspase‐1 activity in the spleen and liver in response to lipopolysaccharide (LPS) challenge. These findings provide new insights into how COX‐2 regulates the activation of the NLRP3 inflammasome and suggest that it may be a new potential therapeutic target in NLRP3 inflammasome‐related diseases. J. Cell. Physiol. 230: 863–874, 2015. © 2014 Wiley Periodicals, Inc.